Changes in Physical Activity and Depressive Symptoms During COVID-19 Lockdown: United States Adult Age Groups - Kim, Amy Chan Hyung; Du, James; Andrew, Damon P. S. (Frontiers in Psychology, 2022)
This study investigates: (1) the changes in three major health-related factors - physical activity, non-physical-activity health behavior (i.e., diet quality, alcohol consumption, smoking, sleep quality), and depressive symptoms, and (2) how changes in physical activity were associated with changes in one’s depressive symptoms among young adults, middle-aged adults, and older adults while controlling non-physical-activity health behavior and sociodemographic characteristics among young, middle-aged, and older adults before and after the COVID-19 outbreak lockdown in the United States. A total of 695 participants completed an online questionnaire via MTurk, and participants were asked to recall their physical activity, depressive symptoms, and non-physical-activity health behavior status in January and May of 2020. The IPAQ-SF was used to evaluate individuals’ physical activity, while the CES-D-10 was used to assess depressive symptoms. Covariates included non-physical-activity health behavior and sociodemographic factors. A Bayesian significance testing of changes was used to examine significant changes in physical activity, non-physical-activity behavior, and depressive symptoms in each age group while Bayesian regression analysis was employed to examine how the changes in physical activity were associated with respondents’ depressive symptoms while controlling for individual NHB and sociodemographic characteristics. The results showed that the participants tended to maintain their physical activity levels after the lockdown despite significant increases in sitting time among young and older adults. Decreases in moderate physical activity frequency were associated with a higher level of depressive symptoms (R2=17.1%). Although young and middle-aged cohorts experienced fewer differences in depressive symptoms compared to their counterparts in the older group, we found no significant heterogeneity effects in the relationships of interest across all age groups. Considering different influences of physical activity on depressive symptoms depending on different levels of activity and ages, more randomized clinical trials with program-based intervention studies should be conducted with different physical activity programs for different age populations.